Imaging Mass Spectrometry Protocols for Mass Microscopy - Setou, Mitsutoshi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2010)
Addressing the widespread need for a practical guide to imaging mass spectrometry (IMS), this book presents the protocols of IMS technology. As that technology expands, research groups around the world continue its development. Pharmaceutical companies are using IMS for drug analyses to study pharmacokinetics and medical properties of drugs. Drug research and disease-related biomarker screening are experiencing greater use of this technology, with a concurrent increase in the number of researchers in academia and industry interested in wider applications of IMS. Intended for beginners or those with limited experience with IMS technology, this book provides practical details and instructions needed for immediate know-how, including the preparation of animal tissue samples, the application of a matrix, instrumental operations, and data analysis, among others. By describing the foundations of IMS, this volume contributes to the ongoing development of the field and to progress in human health.
Innovation of Imaging Mass Spectrometry -- IMS as an Historical Innovation -- Planning the Sample Preparation -- Guide to Planning the Sample Preparation Step -- Sample Preparation -- Animal Care and Tissue Sample Extraction for IMS -- Preparing Biological Tissue Sections for Imaging Mass Spectrometry -- Matrix Choice -- Methods of Matrix Application -- Matrix Application with ImagePrep -- Instrumental Operation for IMS -- Method of Operating AXIMA-QIT as Imaging Instrument -- Analysis of Measurement Data -- Ion Image Reconstruction Using BioMap Software -- Statistical Procedure for IMS Data Analysis -- Statistical Analysis of IMS Dataset with ClinproTool Software -- Applications of MALDI-IMS -- Imaging of Cultured Cells by Mass Spectrometry -- TLC-Blot-MALDI-IMS -- IMS Applications Provided by Manufacturers -- Applied Biosystems -- Bruker Daltonics -- Imaging and Molecular Identification of Biomolecules on Tissue Sections with AXIMA-QIT: Shimadzu Corporation -- MALDI Imaging with Ion-Mobility MS: Waters Corporation -- Comparison of SIMS and MALDI for Mass Spectrometric Imaging -- Comparison of SIMS and MALDI for Mass Spectrometric Imaging.
Keywords: Life sciences; Toxicology; Mass spectrometry; Radiology, Medical; Cytology; Microscopy; Cytology -- Research_xMethodology.; Life Sciences; Biological Microscopy; Cell Biology; Biological Techniques; Imaging / Radiology; Mass Spectrometry; Pharmacology/Toxicology.